2020
DOI: 10.3390/ijerph17051803
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the Growing Water, Carbon and Ecological Footprints of the Chinese Diet from 1961 to 2017

Abstract: In the past decades, food consumption in China has undergone a rapid increase and a significant structure transition, as a result of population growth and economic development. The food system is increasingly threatening the environment by depleting water resources, deteriorating water bodies, aggravating climate change, degrading ecosystems, etc. It is significant to understand how food consumption affected the environment and how its impacts were driven in the historical period. This study reveals the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
0
40
0
1
Order By: Relevance
“…The major findings of this study reveal that globalization does not confirm the positive association with an ecological footprint, increasing population causes to reduce ecological and carbon footprint (Ahmed, Wang et al 2019). Cao, Chai et al (2020) concluded that the increase in population significantly reduces the biodiversity and ecosystem. Further see Figure 2 in order to understand the time trend of reference citations.…”
Section: Figure 1: Reference Co-citation Map Visualizationmentioning
confidence: 59%
“…The major findings of this study reveal that globalization does not confirm the positive association with an ecological footprint, increasing population causes to reduce ecological and carbon footprint (Ahmed, Wang et al 2019). Cao, Chai et al (2020) concluded that the increase in population significantly reduces the biodiversity and ecosystem. Further see Figure 2 in order to understand the time trend of reference citations.…”
Section: Figure 1: Reference Co-citation Map Visualizationmentioning
confidence: 59%
“…Cao et al conclude that from 1961 to 2017, the per capita energy intake of Chinese residents has more than tripled. At the same time, food consumption has shifted from cereals to meat products, especially red meats [18]. Therefore, at present, China's food consumption problem has gradually changed from an absolute quantity shortage to a structural imbalance, and one of the most important issues is the excessive intake of meat.…”
Section: Introductionmentioning
confidence: 99%
“…The diet consumption has changed from starchy foods to animal-based for the Chinese. From 1961 to 2017, the per capita calorie intake of red meats increased by 16 times [ 33 ].…”
Section: Discussionmentioning
confidence: 99%